Persepsi Peserta Didik Terhadap Pemanfaatan Aplikasi Instagram Sebagai Sumber Belajar pada Mata Pelajaran Fisika Kelas XI di SMA Negeri 1 Painan - Agma, Asty Raisha; Hidayati, Abna; Zuliarni, Zuliarni; Amilia, Winanda (Lembaga Intelektual Muda (LIM) Maluku, 2024)
Social media can be used as a modern learning resource, one of which is the Instagram application. Because users can access learning content from experts or users with certain areas of knowledge and skills. Instagram is a source of learning because the content presented entertains and educates students. This study aims to describe the availability of Instagram content, the relevance of Instagram content, and the improvement of individual learning in students. This type of research is quantitative descriptive research, the sample of this research is 40 students in grade XI. Data collection using a closed questionnaire with 30 questions. The results of the study concluded that the perception of grade XI students of SMA Negeri 1 Painan towards the use of the Instagram application as a learning resource in Physics subjects was reviewed from the availability of Instagram content of 78%, which was in the strong category, while in terms of the relevance of Instagram Content 78.55% was also in the strong category, and in terms of increasing individual learning, 77.3% was also categorized as strong. Based on the above findings, it can be concluded that Instagram has become a significant learning resource in Physics Learning. Varied and creative Instagram content can help students learn and can motivate students